2018
DOI: 10.5498/wjp.v8.i5.125
|View full text |Cite
|
Sign up to set email alerts
|

Women who suffer from schizophrenia: Critical issues

Abstract: Many brain diseases, including schizophrenia, affect men and women unequally - either more or less frequently, or at different times in the life cycle, or to varied degrees of severity. With updates from recent findings, this paper reviews the work of my research group over the last 40 years and underscores issues that remain critical to the optimal care of women with schizophrenia, issues that overlap with, but are not identical to, the cares and concerns of men with the same diagnosis. Clinicians need to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 182 publications
(170 reference statements)
1
24
0
4
Order By: Relevance
“…It is an important cause of osteoporosis and has been suspected of contributing to breast cancer risk [23]. Because of gender differences in immunity, the agranulocytosis induced by clozapine is thought to be more frequent in women than in men [24].…”
Section: Gender Differences In Schizophreniamentioning
confidence: 99%
See 3 more Smart Citations
“…It is an important cause of osteoporosis and has been suspected of contributing to breast cancer risk [23]. Because of gender differences in immunity, the agranulocytosis induced by clozapine is thought to be more frequent in women than in men [24].…”
Section: Gender Differences In Schizophreniamentioning
confidence: 99%
“…There is some evidence for boosting the dose of antipsychotic medication during periods of lower estrogenic concentration. Alternatively, estradiol or selective estrogen receptor modulators can be added to the drug regimen to reduce symptoms and perhaps also to permit a reduction of antipsychotic dose and, in this way, alleviate antipsychotic adverse effects [24].…”
Section: Gender Differences In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Several research groups have tried to delineate and differentiate clinical subtypes found in DD populations [27,28]; a few gender differences have been found among the subtypes. Some gender differences in comorbidity have also been suggested; in women, comorbid psychotic and depressive symptoms after menopause can be attributed to the loss of estrogen [72,73]. Very few studies have investigated gender differences in treatment response in DD populations, although response to antipsychotics appears to be roughly similar in men and women [24].…”
Section: Discussionmentioning
confidence: 99%